DEGRADASI ZAT WARNA RHODAMIN B MENGGUNAKAN SINTESIS FOTOKATALIS ZnO/NiFe2O4 DAN DIAPLIKASIKAN PADA - Mawarni, Tri; H.C, Fadarina; Aznury, Martha; Taufik, Muhammad (KINETIKA, 2021)
ZnO/NiFe2O4 nanoparticles were synthesized by chemical co-precipitation method and were calcied at 500 0C for 5 h. The Composites synthesis within ratios of zinc oxide to nickel ferrite of 1:0,1, 2:0,1 and 3:0,1. The adsorption and photocatalytic activity of The removal of ZnO/NiFe2O4 were systematically investigated using Rhodamine B and waste water pulp and paper indsutry solution as a model contaminant. Rhodamine B (10 mg/L) and waste water pulp and paper indsutry solution by ZnO/NiFe2O4 (2:0.1) after 2 h reached 98,71% under LED lamp and 91,85% under solar light irradiation for Rh, and after 3 h reached 28,03% under LED lamp for lignin . •OH and h+ play important roles in the decolorization of RhB solution by NiFe2O4/ZnO under simulated LED lamp and solar light irradiation. The adsorption kinetics pattern under conditions of LED lamp and sunlight follows first order kinetic adsorptions.